P209 Specialist respiratory pharmacist case management copd medicines optimisation clinics: implementation and outcomes. (15th November 2016) - Jones, C; Miller, R; Sharkey, R; Friel, A; Clifford, D; Darcy, C; Moore, B; Hall, M
Abstract : Introduction and objectives: In line with 'Transforming Your Care' (restructuring of healthcare provision in Northern Ireland) and the Global Initiative for Chronic Obstructive Lung Disease (GOLD) strategy, this project brought specialist trust pharmacist-led medicines optimisation case management clinics to COPD patients in primary care. The aim of the project was to achieve sustained medicines optimisation with associated improved patient outcomes. Method: An initial process mapping event resulted in establishing the existing COPD patient pathway between primary and secondary care. This informed the decision to base clinics in GP surgeries where the pharmacist: determined disease stage (GOLD classification); assessed medication adherence; established COPD medication appropriateness; prescribed COPD medications and smoking cessation; determined whether antibiotic prescribing was guideline-informed; and made appropriate referrals to primary and secondary care healthcare professionals. A 30-day telephone follow-up by the pharmacist involved reassessment of adherence, symptom scores and medication appropriateness. COPD exacerbations, antibiotic prescribing and unplanned hospital admissions were further recorded over 12 months. All data were analysed using SPSS Version 22. Results: Results for a patient cohort seen over four months (n = 360) demonstrated: statistically significant improvements in COPD medication appropriateness and adherence (Wilcoxon Signed Rank Test, p < 0.001, n = 360); improvement in COPD symptoms (MRC Breathlessness and CAT score); and reduced guideline-informed antibiotic prescribing (12 months post baseline review). Projected annual drug cost savings were £235k. Sixty-eight percent of patients had experienced one or more COPD exacerbations over the year prior to clinic attendance reducing to 50% during the 12 months post-intervention. Non-elective COPD-related hospital admissions also decreased (9.2% versus 5.3% over 12 months). Conclusion: Providing specialist hospital pharmacist COPD clinics in primary care resulted in safe and cost-effective medication use with improved patient outcomes 12 months post review.